Assessing Effectiveness of Mnemonics for Tertiary Students in a Hybrid Introductory Statistics Course. Issue 1 (2nd January 2017) - Mocko, Megan; Lesser, Lawrence M.; Wagler, Amy E.; Francis, Wendy S.
ABSTRACT: Mnemonics (memory aids) are often viewed as useful in helping students recall information, and thereby possibly reducing stress and freeing up more cognitive resources for higher-order thinking. However, there has been little research on statistics mnemonics, especially for large classes. This article reports on the results of a study conducted during two consecutive fall semesters at a large U.S. university. In 2014, a large sample ( n = 1487) of college students were asked about the usefulness of a set of 19 published statistics mnemonics presented in class, and in 2015, the students ( n = 1468) were presented 12 mnemonics related to inference and then asked whether or not they used mnemonics on that exam. This article discusses how students assess the usefulness of mnemonics and evaluates the relationship between using mnemonics and reducing anxiety. Additionally, the relationship between mnemonic usage and learning outcomes achievement will be discussed, along with this study's limitations and implications for teaching.